The "Baependi Heart Study": the real history and the development of new strategies for health promotion in childhood education / O "Estudo do Coração de Baependi": a história real e o desenvolvimento de novas estratégias para a promoção da saúde na educação infantil - Camila Maciel de Oliveira; Flávia Mesquita Soares; Ana Beatriz Clemente Gonçalves; Beatriz Elizabeth Bagatin Veleda Bermudez; Anderson Ulbrich; Edison Almeida Tizzot; Carlos Alberto Mourão Júnior; Rafael de Oliveira Alvim (Hospital de Clínicas de Itajubá, 2018)
The "Baependi Heart Study" started with the Doctoral Thesis of Camila Maciel de Oliveira, in 2005, and it kept working with partnerships among some Universities in Brazil for research and outreach projects. In 2005, José Eduardo Krieger, Alexandre Costa Pereira and Camila Maciel de Oliveira started this pioneer journey in the Laboratory of Genetic and Molecular Cardiology that takes place at the Heart Institute (InCor) at the University of São Paulo (USP). More recently, our group had the opportunity to start projects to discuss some of the cardiovascular risk factors and their prevention among childhood education in Minas Gerais State (Baependi and Juiz de Fora) and Parana State (Curitiba). Why was Baependi considered a desirable choice? The "Baependi Heart Study" started with the Doctoral Thesis of Camila Maciel de Oliveira,1 in 2005, and it kept working with partnerships among some Universities in Brazil for research and outreach projects. In 2005, José Eduardo Krieger, Alexandre Costa Pereira and Camila Maciel de Oliveira had started this journey in the Laboratory of Genetic and Molecular Cardiology that takes place at Heart Institute (InCor) at University of São Paulo (USP). The real history is that Baependi was not the first choice to host the project. At first the study would be in another town near Baependi called Pouso Alegre, Minas Gerais State. It was not possible to develop this project in Pouso Alegre because this kind of study requires a political support, which we did not have there.